(untitled) (South East Asia Journal of Public Health, 2016)
Overweight and obesity are two major health problems that have been recognized worldwide which affect all ages and have many negative health effects. WHO in year 2010 reported that in Egypt the prevalence of overweight among women is 76% compared to 64.5% for male while the prevalence of obesity among women is 48% compared to 22% for male. The aim of the study was to determine the most prevalent skin diseases among the studied over-weight and obese patients and to examine if overweight and obesity are risk factors for skin diseases. A case-control was carried out on 250 overweight and obese patients compared with another 250 normal weight patients as controls. The participants were selected from the outpatient dermatology clinic of Al Hussein University hospital, Faculty of medicine, Alazhar University, Egypt. All patients were subjected to medical history, clinical dermatological examination and measurement of obesity indices. The most prevalent skin diseases among the studied cases were: striae (68.4%), planter hyperkeratosis (61.6%), skin tags (61.2%), acanthosis nigricans (53.6%), intertrigo (53.6%), tinea pedis (41.2%) with statistical significance difference compared to controls. As a result, overweight and obesity might be a risk factor for some skin diseases. Dermatologists must work with primary health care physicians and nutritional specialists to reduce incidence of obesity or reduce the effects of obesity on the skin. South East Asia Journal of Public Health Vol.5(2) 2015: 23-29